SUN-610 Thyroid Storm and Hypoparathyroidism Caused by Anaplastic Thyroid Carcinoma - Oben Perez, Laura (J Endocr Soc, 2019)
Anaplastic Thyroid Carcinoma (ATC) has an incidence of ≤ 2/1,000,000 and mean diagnosis age of 65 years (1). Fewer than 10% are <50 years (2,3). Hypoparathyroidism secondary to destruction of the gland from malignant invasion is rare, accounting for ≤0.7% of all cases (4). The estimated incidence of thyroid storm is <0.2/100,000 per year (5). A 48-year-old woman presents with odynophagia, night sweats, exertional dyspnea, diarrhea and swelling of the neck. A CT shows a large solid mass with cystic pockets in the thyroid measuring 12.5 cm, and multiple lung nodules consistent with metastatic cancer. She is admitted with an initial Burch HB-Wartofsky Score (BWS) of 10. TSH is <0.01 mIU/L; free T4, 2.91 ng/dL; and T3, 6.44 pg/mL. Thyroid fine needle aspiration biopsy shows malignancy with a differential diagnosis of ATC versus metastatic squamous cell carcinoma. A subsequent core thyroid biopsy confirms ATC. The patient developed compressive dyspnea that resulted in hypoxic cardiac arrest followed by atrial fibrillation. She experienced persistent tachycardia, hyperthermia (101.7 F), and coma. She is diagnosed with thyroid storm (BWS of 50). Thyroid antibodies were negative. She responds to high-dose glucocorticoids, beta blockers, and propylthiouracil. Three days later, thyroid function tests, tachycardia, and fever improves, but coma persists. The ATC continues to enlarge rapidly. Fourteen days after admission, she develops hypocalcemia (5.2 mg/dL), and intact Parathyroid Hormone (iPTH) was 6.3 pg/mL. Phosphorus and magnesium are normal. Hypoparathyroidism is attributed to malignant infiltration and destruction of the parathyroid glands. She responds to enteral calcitriol and calcium citrate. Her family opts for comfort measures after 19 days of coma. Conclusion: ATC may present with thyrotoxicosis and progress to thyroid storm. Hypoparathyroidism may occur due to invasion of the parathyroid glands. References: 1. Burke JP, Hay ID, Dignan F, et al. Long-term trends in thyroid carcinoma: a population-based study in Olmsted County, Minnesota, 1935-1999. Mayo Clin Proc 2005; 80:753. 2. Kebebew E, Greenspan FS, Clark OH, et al. Anaplastic thyroid carcinoma. Treatment outcome and prognostic factors. Cancer 2005; 103:1330. 3. Nagaiah G, Hossain A, Mooney CJ, et al. Anaplastic thyroid cancer: a review of epidemiology, pathogenesis, and treatment. J Oncol 2011; 2011:542358. 4. Marcucci G, et al. HypoparaNet: A Database of Chronic Hypoparathyroidism Based on Expert Medical-Surgical Centers in Italy. Calcif Tissue Int. 2018 Aug;103(2):151-163. doi: 10.1007/s00223-018-0411-7. Epub 2018 Mar 6. 5. Akamizu T, et al. Diagnostic criteria, clinical features, and incidence of thyroid storm based on nationwide surveys. Thyroid. 2012 Jul;22(7):661-79. doi: 10.1089/thy.2011.0334. Epub 2012 Jun 12.